Analysis of the Economic Impact of Sustainable Tourism on Increasing Regional Income - Victor Pasalbessy (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the economic impact of sustainable tourism on increasing regional income in Indonesia. Using a quantitative approach with a survey method, primary data was collected through questionnaires distributed to 150 tourism industry players, including hotel managers, restaurants, travel agents, and MSMEs directly involved in the tourism sector. This survey aims to measure the perception of industry players on the impact of sustainable tourism policies on their income. The results of multiple linear regression analysis showed that the variables of sustainable tourism adoption rate, number of tourists, and infrastructure investment had a significant influence on increasing regional income. In particular, the adoption rate of sustainable tourism contributes 45% to the increase in regional income, with an increase in the number of tourists and infrastructure investment also having a positive impact. In addition, the MSME sector that adopts sustainable tourism policies has experienced an increase in revenue, especially in handicrafts, restaurants, and tourist transportation businesses. However, challenges such as lack of coordination between relevant parties and limited infrastructure are still faced. This study recommends increased coordination and investment in infrastructure to strengthen the economic impact of sustainable tourism.